Mobilizing Older Adults: Harnessing the Potential of Smart Home Technologies - Demiris, G.; Thompsonb, H. J. (Yearbook of Medical Informatics, 2012)
This paper highlights the potential of smart home applications to not only assess mobility determinants for older adults in the home environment but also provide the opportunity for tailored interventions.We present a theoretical framework for assessing mobility parameters and utilizing this information to enable behavior change based on the Health Belief Model. We discuss examples that showcase the potential of smart home systems to not only measure but also improve mobility for community dwelling older adults.Mobility is a complex construct that cannot be addressed with a single monitoring approach or a single intervention. Instead, tailored interventions that address specific needs and behaviors of individuals and take into consideration preferences of older adults and potentially their social network are needed to effectively enforce positive behavior change. Smart home systems have the ability to capture details of one’s daily living that could otherwise not be easily obtained; however, such data repositories alone are not sufficient to improve clinical outcomes if appropriate mechanisms for data mining and analysis, as well as tailored response systems are not in place.Unleashing the potential of smart home applications to measure and improve mobility has the potential of transforming elder care and providing potentially cost-effective tools to support independence for older adults. A technologically driven smart home application can maximize its clinical relevance by pursuing interactive features that can lead to behavior change.
Keywords: Aging; mobility; remote sensing technology; self-efficacy